2018
DOI: 10.1039/c8pp00203g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the factors affecting the photothermal therapy potential of small iron oxide nanoparticles over the 730–840 nm spectral region

Abstract: The use of superparamagnetic iron oxide nanoparticles (SPIONs) as a sensitizer in photothermal therapy (PTT) is relatively new and the origin of such a phenomenon is not known. Usually, large crystals and aggregated particles are preferred in the literature, suggesting that these increase the absorbance of particles at the irradiation wavelength, and hence, provide a larger temperature increase. This study has two major goals: identification of the key factors that affect the photo-induced temperature increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…It is well established that thermal ablation triggers necrosis ( Jaque et al, 2014 ). Although some organic molecules can be used as a PS for PTT ( Lv et al, 2020 ), recently metal nanoparticles ( Ke et al, 2011 ; He et al, 2014 ), metal oxide nanoparticles ( Chu et al, 2013 ; Bilici et al, 2018 ), and quantum dots ( Liang et al, 2018 ; Hashemkhani et al, 2020 ), especially with significant absorbance at near-infrared (NIR) for both better tissue penetration and safety due to its nonionizing nature ( Jaque et al, 2014 ), are preferred. Light-to-heat conversion efficiency, dark toxicity, selective tumor accumulation, photostability, and effective heating of the whole tumor are factors to consider for PTT.…”
Section: Photodynamic and Photothermal Therapymentioning
confidence: 99%
“…It is well established that thermal ablation triggers necrosis ( Jaque et al, 2014 ). Although some organic molecules can be used as a PS for PTT ( Lv et al, 2020 ), recently metal nanoparticles ( Ke et al, 2011 ; He et al, 2014 ), metal oxide nanoparticles ( Chu et al, 2013 ; Bilici et al, 2018 ), and quantum dots ( Liang et al, 2018 ; Hashemkhani et al, 2020 ), especially with significant absorbance at near-infrared (NIR) for both better tissue penetration and safety due to its nonionizing nature ( Jaque et al, 2014 ), are preferred. Light-to-heat conversion efficiency, dark toxicity, selective tumor accumulation, photostability, and effective heating of the whole tumor are factors to consider for PTT.…”
Section: Photodynamic and Photothermal Therapymentioning
confidence: 99%
“…Studies show that hyperthermia increases the efficacy of standard cancer treatments. When used in combination with chemotherapy, radiotherapy or radiofrequency ablation, or photothermal therapy, the final outcome of the combined therapy would be more beneficial to the patient, although in clinical practice, physicians are reluctant to use these methods [ 136 , 153 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, SPIONs were observed to be good candidates for photothermal and photodynamic therapy, using near-infrared (700–2000 nm) laser excitation of the nanomaterial. For these therapies, SPIONs are theoretically preferred in larger clusters, although studies have shown that they can yield up to 12 °C temperature increase even in the ultrasmall range (4–5 nm SPIONs at 785 nm laser wavelength, 800 mW power for 20 min) [ 136 ]. The study concluded that ultrasmall SPIONs can also produce heat by excitation with wavelengths smaller than near infrared and that the heating efficacy depends on the laser power.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The CoFe 2 O 4 NPs could be efficient and desirable nanomaterials for combined MHT. SPION, which have been recognized as MHT agents, have been recently utilized as photothermal agents as well [109,110]. One group [111] designed multi-functional polymeric micelles using HA, docetaxel (DTX), and SPION (HA–SPION–DTX) for combined photothermal chemotherapy.…”
Section: Combined Therapies Using Hyperthermiamentioning
confidence: 99%